Thermogravimetric research into fish and plant semifinished products made of raw and blanched tissues of Azov goby and wheat bran - Prytulska, Nataliia; Fedorova, Dina; Lazarenko, Maxim; Vasylieva, Olena; Yudina, Tatiana (Eastern-European Journal of Enterprise Technologies, 2016)
According to results of thermogravimetric and differentia-thermal studies, we compared characteristics of the amount of adsorption– and capillary-bound moisture in the experimental samples of fish and plant semifinished products, as well as determined the values of activation energy of the molecules of water at different temperatures of moisture removal. By the results of analysis of the DTG peaks, it is established that the largest amount of osmotic– and adsorption-bound moisture is observed in samples made on the base of raw fish raw materials due to the higher degree of hydration of protein molecules in minces. It is found that the application of hydrothermal pre-treatment of muscle, connective and skeletal tissue complex of Azov goby leads to the reduction in the amount of adsorption-bound moisture and decreses the energy of its bond with the product. The use of wheat bran somewhat increases the amount of bound moisture in the fish mince structure as a result of increase in the number of available hydroxyl groups and the formation of macroporous structure, which causes the increase in its hydrofilicity. It is established experimentally that the influence of plant raw materials on the increase in activation energy of the molecules of water for the experimental fish and plant semifinished products is less significant than the use of native fish raw material. The obtained results allow better understanding of the structural changes that occur in the process of drying the fish and plant semifinished products. They might be applied to optimize the drying processs of fish and plant semifinished products and to predict their technological behavior in various food systems, as well as while storing.